AFRICANIZED SPACES IN BRAZIL: SOME REFERENCES OF RESISTANCE, SURVIVAL AND REINVENTIONS - Amador de Deus, Zélia (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2016)
This paper deals with the African diaspora in a context where the Africa brought to the Americas, somehow survived and at the same time, worked as an instrument of survival for Africans and their descendants. In particular, the cultures of African nature, over time, were and are used as political strategies that shape processes of negotiations, highlighting the contemporary Brazilian quilombos as African-like spaces present in the narrative of Brazilian nationality.